Tra attivismo militante, mandato professionale e posizionamento di ricerca. Considerazioni e proposte su l’operatività congiunta nell’accoglienza dei richiedenti asilo - Mugnaini, Martina (Antropologia Pubblica, 2017)
This contribution attempts to bring into focus an explanation on the categories of professionals involved in the Italian reception system for asylum seekers to unveil the interconnections overlapping their professional actions and to offer a interpretative frame for the following remarks. Through a report of a personal professional experience to disclose the intricacy deriving from dual stances and concepts, I stress three considerations deriving from the figures I simultaneously carried out in a reception centre: the one depicted by the mandate as head of projects for social insertion as intercultural mediator, the other as executive director, and the third one, as researcher, in order to probe the impact of the social planning implemented. Briefly, these assumptions consist on a set up of remarks: a proportional relationship between job experience and capability of interpretation of the research data; an inverse relationship between the hierarchical position covered and the level of trust given from interlocutors, and finally, a high probability to fall into operative clashes due to different professional ethics, which can bring to particular professional positions. Conclusively, as a response of this personal work and research experience, I propose an operational process, which could be carried out in collaboration with all the stakeholders involved in the reception system; this means professionals, migrants and local communities, with the aim to reduce the today's inefficiency of the migrants reception model.